Challenges in characterization of transcriptomes of extracellular vesicles and non-vesicular extracellular RNA carriers - Makarova, Julia; Maltseva, Diana; Tonevitsky, Alexander (Frontiers in Molecular Biosciences, 2023)
Since its original discovery over a decade ago, extracellular RNA (exRNA) has been found in all biological fluids. Furthermore, extracellular microRNA has been shown to be involved in communication between various cell types. Importantly, the exRNA is protected from RNases degradation by certain carriers including membrane vesicles and non-vesicular protein nanoparticles. Each type of carrier has its unique exRNA profile, which may vary depending on cell type and physiological conditions. To clarify putative mechanisms of intercellular communication mediated by exRNA, the RNA profile of each carrier has to be characterized. While current methods of biofluids fractionation are continuously improving, they fail to completely separate exRNA carriers. Likewise, most popular library preparation approaches for RNA sequencing do not allow obtaining exhaustive and unbiased data on exRNA transcriptome. In this mini review we discuss ongoing progress in the field of exRNA, with the focus on exRNA carriers, analyze the key methodological challenges and provide recommendations on how the latter could be overcome.